PBMC gene expression profiles of female Bangladeshi adults chronically exposed to arsenic-contaminated drinking water. (April 2020) - Chen, Qiao Yi; Shen, Steven; Sun, Hong; Wu, Fen; Kluz, Thomas; Kibriya, Muhammad G.; Chen, Yu; Ahsan, Habibul; Costa, Max
Abstract: Arsenic, a class I human carcinogen, is ubiquitously found throughout the environment and around the globe, posing a great public health concern. Notably, Bangladesh and regions of West Bengal have been found to have high levels (0.5–4600 μg/L) of arsenic drinking water contamination, and approximately 50 million of the world's 200 million people chronically exposed to arsenic in Bangladesh alone. This study was carried out to examine genome-wide gene expression changes in individuals chronically exposed to arsenic-contaminated drinking water. Our study population includes twenty-nine Bangladeshi female participants with urinary arsenic levels ranging from 22.32 to 1828.12 μg/g creatinine. RNA extracted from peripheral blood mononuclear cells (PBMCs) were evaluated using RNA-Sequencing analysis. Our results indicate that a total of 1, 054 genes were significantly associated with increasing urinary arsenic levels (FDR p < 0.05), which include 418 down-regulated and 636 up-regulated genes. Further Ingenuity Pathway Analysis revealed potential target genes ( DAPK1, EGR2, APP ), microRNAs (miR-155, -338,  −210) and pathways ( NOTCH signaling pathway) related to arsenic carcinogenesis. The selection of female-only participants provides a homogenous study population since arsenic has significant sex dependent effects, and the wide exposure range provides new insight for key gene expression changes that correlate with increasing urinary arsenic levels. Graphical abstract: Image 1 Highlights: RNA-Sequencing was performed using peripheral blood mononuclear cells from female Bangladeshi adults from the HEALS cohort. Urinary arsenic levels of the study participants ranged from 22.32 to 1828.12 μg/g creatinine. A total of 1, 054 genes were significantly associated with increasing urinary arsenic levels (FDR p < 0.05). Ingenuity Pathway Analysis revealed key cancer-related genes and pathway including  DAPK1,   EGR2,   APP, and the  NOTCH1  signaling pathway. Abstract : Main finding : Our study reveals that increase in urinary arsenic levels is correlated with significant changes in cancer-related gene expression in female Bangladeshi adults.